Funding and Proposals of the European Commission for Resources in the Field of European Defense Policy - Liakopoulos, Dimitris (Studies in Law and Justice, 2025)
The present paper aims to highlight another stage of integration, that is, the field of defense policy. The investigation is based on the White Paper that was adopted in March of 2025 and on the related new proposals that it offered for defense financing. The main topic is the European resources that each EU Member State can offer and especially in our days that the need is even higher given the situation in Ukraine. News and/or steps backwards in the defense sector is still very early to say. It depends on the Member States to take a position on the matter as well as to decide whether defense is truly one of the leading policies in the context of the EU.